Pelaksanaan Pembiayaan Konstruksi BTN IB Dengan Akad Musyarakah Pada PT. Bank Tabungan Negara (Persero) Tbk Kantor Cabang Syari’Ah Pekanbaru - Nurjannah, Ayu (Simbur Cahaya, 2019)
This thesis discusses the implementation of the construction financing in Musyarakah contract in Islamic banking practices. Musyarakah financing is a venture capital partnership between the bank and its customers that cannot simply be removed from regular financing paradigm. So that, the provisions concerning the financing of working capital in general are also applied in the implementation of Musyarakah financing. Any financing provided by the bank to the customer would raise the risk of financing, so does Musyarakah financing. This study formulated two formulations of problems; (1) How is the implementation of the construction financing BTN iB with Musyarakah agreement with PT. Bank Tabungan Negara (Persero) Branch Shariah Pekanbaru?, (2) What are the obstacles and problem solvings in the implementation of construction financing BTN iB with Musyarakah agreement with PT. Bank Tabungan Negara (Persero) Branch Shariah Pekanbaru?. This study uses empirical juridical approach. The data used are primary data in the form of interviews and documents and library studies and secondary data obtained from primary law materials and secondary law. The data were then analyzed qualitatively